فعل قلب: اسلام اور سائنس کی روشنی میں تقابلی جائزہ: Heart functioning according to Islam & Science: comparative study - Dr. Sajila Kousar; Muneeba Shafiq (MEI, 2023)
Heart is a vital organ of human body. Its main functioning is considered to pump and supply blood to whole body. But a deep and comparative study of Qur’an and Sunnah extends its role to many other spheres. Qur’an declares the heart a pivot for decision making. We can not deny this reality that the contradiction between Qur’an and science is just a paradox. The need of the hour is to analyse the divine declaration of Qur’an on logical basis and reinspect scientific theories from the very beginning and compare both the antinomy realities. This concept is also emphasized by Dr Allama Muhammad Iqbal in the preface of ‘‘The reconstruction of religious thoughts in Islam’’…… ‘‘the day is not far off when religion and society may discover hitherto unsuspected mutual harmonies’’. This paper will highlight a comparative study of heart functioning according to Islamic injunstions and finally conclude that how a reasonable heart can play its role in world peace.